Implementation of Human Concern in Education and Empowerment of Earthquake Victims in Cianjur Regency - Sutarman, Sutarman; Herlina, Herlina; Mulyeni, Sri; Riyanto, Slamet; Sukanti, Lina (The International Journal of Education Management and Sociology, 2022)
The purpose of this study was to determine the level of public awareness of the earthquake victims that occurred in the Cianjur Regency. Want to analyze the educational process of the Cianjur earthquake victims and want to know the empowerment of each volunteer for the earthquake victims. The research method used is qualitative which describes the phenomena that occur in the research location. Data collection techniques in the form of direct observation of the community and environment around the disaster. Interviews with the victim community, officials, and other volunteers who were met at the research location. Documentation studies from various sources, such as the internet, information from fellow volunteers, and various Watch-Ap groups. Conclusion: (1). The implementation of the level of concern from all the people of West Java, Jakarta, and Banten are very enthusiastic to help and assist, as evidenced by the various institutions, communities, and vehicles carrying supplies in the form of funds as well as food and clothing, thronging the earthquake victim area. (2). Implementation of education directed at school-age children in the form of volunteers in the form of Trauma Healing in the form of reading the Koran using the Iqro model, quizzing learning questions, singing, and giving gifts in the form of snacks and textbooks. Community empowerment in the form of Strengthening faith and destiny as to why earthquakes occur, and information about knowledge of how earthquakes occur. Distribution of groceries, women's clothing, men's clothing, and children's clothing, and free medical and health care